2021
DOI: 10.3390/ijerph18189482
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of 24-Hour Movement Behaviors in Preschool Children Using Wrist-Worn and Thigh-Worn Accelerometers

Abstract: In recent years, more attention has been paid towards the study of 24-h movement behaviors (including physical activity (PA), sedentary behavior (SB) and sleep) in preschoolers instead of studying these behaviors in isolation. This study aimed to evaluate the feasibility of using wrist- vs. thigh-worn accelerometers and to report accelerometer-derived metrics of 24-h movement behaviors in preschoolers. A convenience sample of 16 preschoolers (50.0% boys, 4.35 years) and one of their parents were recruited for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Similar concerns have been raised with the use of the activPAL due to skin irritation in previous research [ 53 ]. However, further studies have reported that the activPAL was generally accepted [ 24 , 28 ], with minimal reports of removal of the device due to the dressing of the device being uncomfortable for the child [ 24 ]. Despite this, in some research studies it may be that, for accuracy reasons, devices must be attached to the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar concerns have been raised with the use of the activPAL due to skin irritation in previous research [ 53 ]. However, further studies have reported that the activPAL was generally accepted [ 24 , 28 ], with minimal reports of removal of the device due to the dressing of the device being uncomfortable for the child [ 24 ]. Despite this, in some research studies it may be that, for accuracy reasons, devices must be attached to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently no practical recommendations for the measurement of movement behaviours of pre-school children and limited research exploring the acceptability and feasibility of tools used for this purpose [ 22 , 23 ]. Studies examining acceptability have primarily used survey based research, whereby parents or researchers rate sentences such as ‘ the device was uncomfortable to wear ’ [ 24 , 25 , 26 , 27 , 28 ] or through researcher observation [ 29 ]. Whilst these studies are informative in inferring the practical acceptability of devices, there is a need for more qualitative research to understand how different tools are perceived and accepted in the target population to ensure they are appropriate and accessible prior to use [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is not known if there are temporal variabilities in PA, SB, and SL of preschoolers’ issues that remain unaddressed and await future research. Nonetheless, future research on the 24-h behaviours of PA, SB, and SL should employ a combination of subjective (appropriately developed questionnaires) and objective (such as accelerometers) methods [ 72 , 73 ] for a more complete understanding of 24-h movement behaviours in preschoolers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the validity remains unclear, these algorithms have been used in other studies. Little evidence is currently available regarding the validity of these algorithms for this age-group, they are being used in similar research ( 24 ), and validation in youth and adults is promising ( 25 ).…”
Section: Methodsmentioning
confidence: 99%